2021
DOI: 10.1155/2021/5574010
|View full text |Cite
|
Sign up to set email alerts
|

Astragali Radix Contributes to the Inhibition of Liver Fibrosis via High-Mobility Group Box 1-Mediated Inflammatory Signaling Pathway

Abstract: Astragali Radix (AR), the dried root of Astragali Radix membranaceus (Fisch.) Bge. or Astragali Radix membranaceus (Fisch.) Bge. var. mongholicus (Bge) Hsiao, is a commonly used traditional Chinese medicine for the treatment of liver diseases. This study aimed to comprehensively evaluate the pharmacological action and explore the potential mechanism of AR on liver fibrosis. Rats were administered with carbon tetrachloride for eight weeks, followed by oral treatment with AR for six weeks. The efficacy was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In this experiment, BDL rats showed up-regulation of hepatic protein and gene expression of HMGB1 and gene expression of RAGE, which is in harmony with the study by Wen et al 42 . These findings suggest that the HMGB1/RAGE pathway may contribute to the molecular mechanisms of cholestasis-induced liver fibrosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this experiment, BDL rats showed up-regulation of hepatic protein and gene expression of HMGB1 and gene expression of RAGE, which is in harmony with the study by Wen et al 42 . These findings suggest that the HMGB1/RAGE pathway may contribute to the molecular mechanisms of cholestasis-induced liver fibrosis.…”
Section: Discussionsupporting
confidence: 90%
“…Wu et al 65 reported that TGF-β1 expression in HSCs could be promoted via activated JNK. Furthermore, Wen et al 42 demonstrated that activated MAPKs, including JNK, triggered collagen expression in HSCs in fibrotic rat livers induced by CCL 4 . More importantly, the same study found that MAPKs' fibrotic effects were mediated through the HMGB/RAGE pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Astragali Radix (AR), curcumin, oxymatrine (OMT), ethyl pyruvate (EP), insulin-like growth factor 1 (IGF-1), chloroquine (CQ), as well as quercetin have may decrease CCl4-induced liver inflammation via suppressing HMGB1/TLR4/NF-κB axis(Dai et al 2018 ; Li et al 2016 ; Tu et al 2012 ; Wen et al 2021 ; Zhang et al 2018b ; Zhao et al 2016 ; Zhao et al 2021 ). The use of AR can greatly decrease the generation of type 1 collagen in mice via inhibiting HSCs activation and collagen secreted via HMGB1-RAGE-c-Jun pathway(Wen et al 2021 ). γ-mangostin (γ-man) induces the activation of Sirtuin 3 (Sirt3), leading to an anti-fibrotic action.…”
Section: Hmgb1 Translocation and Secretionmentioning
confidence: 99%
“…DS could downregulate TNF-α, COX-2, inducible nitric oxide synthase (iNOS), and ILs by activating Nrf2, thus inhibiting the inflammatory response . Other TCMs included in YXB also have good anti-inflammatory effects. However, as a complex Chinese traditional patent medicine, the anti-inflammatory mechanisms of YXB are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%